Effects of tetrandrine on functions and ultrastructure of alveolar macrophages in smoke inhalation-injured rabbits. - Zhang Min; Huang Yue-Hua; Li Ao; Yang Zong-Cheng (Acta Pharmacologica Sinica; Vol 14, No 6 (November 1993): Acta Pharmacologica Sinica, 2016)
A rabbit model with severe smoke inhalation injury was used to explore the effects of tetandrine (Tet) on the release of inflammatory mediators and the level of [Ca2+]i in alveolar macrophages (AM) as well as on the ultrastructural changes. It was found that Tet reduced the number of white blood cells (WBC) in bronchoalveolar lavage fluid, inhibited the release of LTB4 and O2-. from AM, and increased the [Ca2+]i in AM. The changes in size, pseudopod, and lysosome evacuation in AM treated with Tet were smaller than those in the AM from the untreated. These results suggest that Tet may alleviate the pulmonary injury through inhibiting the activation of AM.